Poly(octamethylene citrate) Modified with Glutathione as a Promising Material for Vascular Tissue Engineering - Flis, Agata; Trávníčková, Martina; Koper, Filip; Knap, Karolina; Kasprzyk, Wiktor; Bačáková, Lucie; Pamuła, Elżbieta (Polymers, 2023)
One of the major goals of vascular tissue engineering is to develop much-needed materials that are suitable for use in small-diameter vascular grafts. Poly(1,8-octamethylene citrate) can be considered for manufacturing small blood vessel substitutes, as recent studies have demonstrated that this material is cytocompatible with adipose tissue-derived stem cells (ASCs) and favors their adhesion and viability. The work presented here is focused on modifying this polymer with glutathione (GSH) in order to provide it with antioxidant properties, which are believed to reduce oxidative stress in blood vessels. Cross-linked poly(1,8-octamethylene citrate) (cPOC) was therefore prepared by polycondensation of citric acid and 1,8-octanediol at a 2:3 molar ratio of the reagents, followed by in-bulk modification with 0.4, 0.8, 4 or 8 wt.% of GSH and curing at 80 °C for 10 days. The chemical structure of the obtained samples was examined by FTIR-ATR spectroscopy, which confirmed the presence of GSH in the modified cPOC. The addition of GSH increased the water drop contact angle of the material surface and lowered the surface free energy values. The cytocompatibility of the modified cPOC was evaluated in direct contact with vascular smooth-muscle cells (VSMCs) and ASCs. The cell number, the cell spreading area and the cell aspect ratio were measured. The antioxidant potential of GSH-modified cPOC was measured by a free radical scavenging assay. The results of our investigation indicate the potential of cPOC modified with 0.4 and 0.8 wt.% of GSH to produce small-diameter blood vessels, as the material was found to: (i) have antioxidant properties, (ii) support VSMC and ASC viability and growth and (iii) provide an environment suitable for the initiation of cell differentiation.
Keywords: adipose tissue-derived stem cells (ASCs); cytocompatibility; poly(alkylene citrates); vascular smooth-muscle cells (VSMCs); glutathione (GSH); citric acid; vascular tissue engineering; poly(1,8-octametylene citrate)